Pendekatan Sains dalam Memahami Perjalanan Isra Nabi Muhammad SAW dengan Teori Relativitas - Sabrina Kaneishia; Hanim Isti Fadah; Rany Angeline Yulianto; Atika Yulandari; Bambang Supriadi (Pendidikan Fisika Universitas Nurul Huda, 2024)
The topic was chosen because of the similarity of the concepts of the theory of relativity with the characteristics of the Prophet Muhammad's Israeli journey, namely the speed that exceeds the speed of light. The method used in this research is a qualitative approach with a focus on literature review. The data source comes from a literature review related to Isra. Furthermore, researchers conducted simulations to generate the necessary data using the MATLAB algorithm. The results obtained are the relationship of length contraction that occurs is directly proportional to the travel time in the Isra event. The Isra event of the Prophet Muhammad SAW can be understood with a scientific approach and spiritual aspects to provide a more complete and comprehensive understanding. Future research is expected to combine the theory of relativity with other concepts other than in science to explain the phenomenon of Isra' Mi'raj more comprehensively